Effect of Growing Media Composition and Potassium Fertilizer Dosage on the Growth and Yield of Tomato (Lycopersicum esculentum L.) - Adhila Zulfa Chairunnisa; Sutini Sutini; Nora Augustien (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The market demand increase in tomato has not been matched by the tomato production. One of the factors of tomato plant production is less than optimal due to lack of potassium nutrition and improper planting media, causing flower loss. The aim of this current study is to evaluate the effect of planting media composition and the dose of KCl fertilizer on the growth and yield of tomato plants. The research was conducted in Jemur Wonosari, Wonocolo District, Surabaya City, East Java, from November 2023 to February 2024. The experiment was designed according to a Completely Randomized Design with two factors, each consisting of 4 levels, and was executed in triplicates. The composition of planting media was the first factor at different ratio of S:GM:RHC with S =soil, RHC = rice husk charcoal, and GM = goat manure. There were 4 media compositions, namely M0 (1:0:0), M1 (1:1:1), M2 (1:1:2), and M3 (1:2:1). The dosage of KCl fertilizer (K) was the second factor, included K0 = 150 kg/ha, K1 = 150 kg/ha, K2 = 200 kg/ha, and K3 = 250 kg/ha. The results showed that the treatment combination of planting media composition M1 (1:1:1) + KCl dose 150 kg/ha was able to accelerate the flowering time of tomato plants.